2020
DOI: 10.1590/1519-6984.208863
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution in marine invertebrates in rocky shore of Araucania Region (38° S, Chile)

Abstract: Abstract The rocky shores in Chile have a wide invertebrate species diversity, that include species with marked abundances in determined regions. The aim of the present study is to analyse the spatial distribution pattern in different marine invertebrate species in rocky shore of Araucania region, considering if these species have random, uniform or associated patterns, and extrapolate if these patterns have Poisson, binomial or negative binomial distribution respectively. The results revealed the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(19 reference statements)
2
2
0
Order By: Relevance
“…This association of an aggregated pattern with negative binomial distribution has been reported by classic literature on benthic fauna [25], as well as by applied entomological studies [22]. The same pattern was reported for inland water crustaceans in Chilean Patagonia [24,26], for intertidal invertebrates on the north Patagonian coast [27], and for the gastropod Echinolittorina peruviana on the rocky shore of Antofagasta [12]. The existence of uniform distribution in four of the 19 sampling events is probably due to interspecific interactions, most likely competition with other species that share the same ecological niche [5][6][7].…”
Section: Discussionsupporting
confidence: 83%
“…This association of an aggregated pattern with negative binomial distribution has been reported by classic literature on benthic fauna [25], as well as by applied entomological studies [22]. The same pattern was reported for inland water crustaceans in Chilean Patagonia [24,26], for intertidal invertebrates on the north Patagonian coast [27], and for the gastropod Echinolittorina peruviana on the rocky shore of Antofagasta [12]. The existence of uniform distribution in four of the 19 sampling events is probably due to interspecific interactions, most likely competition with other species that share the same ecological niche [5][6][7].…”
Section: Discussionsupporting
confidence: 83%
“…Aggregation, recorded in all three taxa here, was documented in Funisia and Parvancorina populations collected from the Ediacara Hills, South Australia (Coutts et al 2018;Mitchell et al 2020). The prevalence of aggregation for many of the White Sea taxa is consistent with modern marine benthic invertebrates, whose populations are often aggregated as a result of reproductive or environmental controls (e.g., Schmidt 1982;Keough 1984;Carlon and Olson 1993;Rodríguez et al 1993;Miron et al 1999;Manríquez and Castilla 2007;Ambroso et al 2013;Hooper and Eichhorn 2016;Lesneski et al 2019;De los Ríos and Carreño 2020;Rodriguez-Perez et al 2020). Furthermore, Charniodiscus and Fractofusus from the Avalon Assemblage and Ernietta from the Nama Assemblage in Namibia (Gibson et al 2019(Gibson et al , 2021Mitchell et al 2019) have been shown to exhibit aggregation, indicating that this spatial pattern was present, or even common, throughout the Ediacara Biota.…”
Section: Discussionsupporting
confidence: 67%
“…Field works and study site: the ten sites are located in the coastal town of Antofagasta, northern Chile, six sites are located within town, whereas as external group, was included a four sites in a rocky shore located at 20 km of the town, with low or practically null human intervention (Figure 1, Table 1). The studied sites were visited in summer 2019, for each site, was thrown out random (Ríos and Arancibia, 2018; Ríos and Carreño, 2020), 10 * 10 cm quadrants (n = 40 for each site), considering the relative small size of considered species (Underwood, 2004;Underwood and Chapman, 2005;Ahmad et al, 2011;Ríos and Carreño, 2020).…”
Section: Methodsmentioning
confidence: 99%